Sosialisasi Potensi Bencana dan Rekomendasi Mitigasi Kawasan Destinasi Air Terjun di Desa Santong, Kabupaten Lombok Utara - Karyawan, I Dewa Made Alit; Rohani; Hasyim; Jayanegara, I Dewa Gede; Salehudin; Saidah, Humairo; Yasa, I Wayan (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Santong Village, located in North Lombok Regency, has a very potential waterfall tourist attraction. However, this area is also prone to natural disasters such as landslides and flash floods. To improve public understanding of these risks, disaster mitigation socialization activities were carried out aimed at building a protection strategy for waterfall tourist destinations. This activity involved mapping potential risks, collaboration with KKN PMD students and the community, and synergy between agencies to ensure tourism management that is in line with environmental conservation principles. The main focus of this activity is to foster community preparedness and prepare recommendations for disaster mitigation policies that are oriented towards the sustainability and safety of tourist destinations. The implementation process begins with the preparation stage, including preparing an activity plan, forming an implementation team, coordinating with the village government, preparing supporting instruments, reviewing literature, and managing permits. After that, socialization materials were prepared starting from collecting primary and secondary data through interview methods, field observations, and document reviews. The data obtained was analyzed to identify potential threats, response capacity, and develop appropriate mitigation strategies. The socialization was carried out by presenting speakers from the Unram Community Service Team and the Regional Disaster Management Agency (BPBD) of North Lombok Regency, and inviting community participation from various village elements. This activity was also equipped with the delivery of materials, visual presentations, and evaluations in the form of pre- and post-tests to assess the participants' understanding. The activity with participants from village officials and the community with a participation rate reaching 80%. The material presented included a general description of the village, the potential for waterfall tourism, and various disaster risks such as landslides, flash floods, earthquakes, and fallen trees. The results of the analysis showed that the main threats were landslides and flash floods. From the discussions that were held, a number of proposals emerged such as mapping vulnerable areas, compiling evacuation routes, and developing an early warning system. This socialization has proven effective in increasing public awareness of the importance of disaster mitigation, while also encouraging active community participation in maintaining the sustainability and sustainability of tourism in Santong Village.